2014
DOI: 10.1088/0031-9155/59/14/3843
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of the Ingenuity TF PET/CT scanner with a focus on high count-rate conditions

Abstract: This study evaluated the positron emission tomography (PET) imaging performance of the Ingenuity TF 128 PET/computed tomography (CT) scanner which has a PET component that was designed to support a wider radioactivity range than is possible with those of Gemini TF PET/CT and Ingenuity TF PET/MR. Spatial resolution, sensitivity, count rate characteristics and image quality were evaluated according to the NEMA NU 2–2007 standard and ACR phantom accreditation procedures; these were supplemented by additional meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 23 publications
5
68
0
Order By: Relevance
“…The CRC measurements in our phantom study for both standard-and small-voxel reconstructions are consistent with the results of Kolthammer et al (16). Furthermore, the improvement of CRCs for small-voxel reconstructions implies an improved image resolution, which has a direct impact on the interpretation of clinical SUV measurements of small lesions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The CRC measurements in our phantom study for both standard-and small-voxel reconstructions are consistent with the results of Kolthammer et al (16). Furthermore, the improvement of CRCs for small-voxel reconstructions implies an improved image resolution, which has a direct impact on the interpretation of clinical SUV measurements of small lesions.…”
Section: Discussionsupporting
confidence: 91%
“…In current practice, the image voxel size for whole-body 18 F-FDG PET scans is typically around 4 · 4 · 4 mm (7,16). Conti (7) suggested that in combination with new high sensitive TOF PET/CT cameras, the use of reconstructions with smaller voxels might further improve the detection of small lesions.…”
mentioning
confidence: 99%
“…Currently all three major PET vendors have at least one version of a TOF PET/CT system available, with Siemens using LSO, while Philips and GE use LYSO or another lutetium-based scintillator, respectively. The timing resolution for all of these systems (Philips Ingenuity, Siemens mCT, and GE Discovery 690) is in the range of 500–550 ps using 20–25 mm long crystals [2628]. In addition to these three major PET vendors, Toshiba has recently introduced the Celesteion PET/CT system, which achieves a system timing resolution of ~400 ps while also using LYSO crystals [29].…”
Section: Current State-of-art Pet Scannersmentioning
confidence: 99%
“…Images were reconstructed into 36 frames, with all appropriate corrections applied, using either the standard 3-dimensional row-action maximum-likelihood algorithm (3DR) reconstruction protocol as implemented on the Gemini scanner or the latest version of the time-offlight (TF) reconstruction protocol, which comes with Monte Carlo (19)-based scatter correction and will be implemented in the current generation of Philips scanners (Ingenuity TF) (20).…”
Section: Patient Populationmentioning
confidence: 99%